The Mind Of The Ceo - Jeffrey E. Garten
The Mind of the CEO offers unprecedented access to the most dynamic business leaders of our time. Reading this book is like being at the World Economic Forum in Davos, Switzerland-- not at the formal presentations but in the hotel bar afterward, where the microphones are turned off and world-famous business leaders say what they really think. Better still, their confidant, Jeffrey Garten, interprets what they say, telling you how their views relate to each other and the world economy, and noting the many important things left unsaid. A revealing glimpse into the future of business, The Mind of the CEO captures as no other book before it what is in the minds of top business leaders and what it means for all of us.